Clinical characteristics and outcomes of patients with isolated pulmonary embolism. Issue 6 (September 2021) - Lee, Yong Hoon; Cha, Seung-Ick; Shin, Kyung Min; Lim, Jae Kwang; Lee, Won Kee; Park, Ji-Eun; Choi, Sun Ha; Seo, Hyewon; Yoo, Seung-Soo; Lee, Shin-Yup; Lee, Jaehee; Kim, Chang-Ho; et al.
Abstract : N/A: The clinical relevance of concomitant deep vein thrombosis (DVT) in patients with pulmonary embolism remains controversial. The aim of the present study was to assess clinical characteristics of patients with isolated pulmonary embolism, thereby investigating isolated pulmonary embolism related clinical factors. Patients hospitalized for pulmonary embolism who underwent DVT workup within 3 days of pulmonary embolism diagnosis were retrospectively classified into two groups: patients with isolated pulmonary embolism and patients with DVT-associated pulmonary embolism (DVT-PE). The clinical, laboratorial and radiological parameters were compared between the two groups. Of 1012 patients, 322 (31.8%) presented with isolated pulmonary embolism, and 690 (68.2%) presented with DVT-PE. In a multivariate analysis, female sex was an independent factor for predicting isolated pulmonary embolism [odds ratio (OR) 1.69, 95% confidence interval (CI) 1.26–2.26, P  < 0.001], whereas cancer (OR 0.64, 95% CI 0.43–0.96, P  = 0.031), leg pain or swelling (OR 0.08, 95% CI 0.04–0.18, P  < 0.001), and central pulmonary embolism (OR 0.44, 95% CI 0.32–0.59, P  < 0.001) were negatively associated with isolated pulmonary embolism. There were no significant differences between the two groups with regard to risk stratification and short-term prognosis of pulmonary embolism, including adverse outcomes and pulmonary embolism related in-hospital mortality. Of pulmonary embolism patients who underwent imaging tests for DVT, approximately 32% presented with isolated pulmonary embolism. Isolated pulmonary embolism was positively associated with female sex, whereas it was negatively associated with cancer, leg pain or swelling, and central pulmonary embolism. The presence or absence of concomitant DVT did not influence the severity and short-term prognosis of pulmonary embolism.